The View of Medical Intern Students in Achievement Clinical Competency with Learning Mastery Approach in Gorgan school of Medicine: Qualitative Study - mohammad reza yosefi; mitra jodi (Babol University of Medical Sciences, 2020)
Background and Objective: Physician have a fundamental role in keeping and improving society's health and are responsible for all services needed to their proficiency. So as to boosting skills and acquiring clinical competence in line with responsive medical purposes, clinical competence training course (a one- month course) is held in emergency sections. This study with the purpose of evaluating view of medical intern students in achievement clinical competency with Learning Mastery approach in Golestan University of medical sciences. Methods: A qualitative study physician student members Case School of Medicine aimed of situations based on the volume of data the study was collected through in-depth interviews. Transcript extracted van Manen method conceptual thematic content (theme) were extracted from it. Findings: Data analysis necessity of such themes all you need to plan the perfect law and access to social all medical services that include availability of benefits associated with the theme of the research training primarily training time Research Services patients day, increasing hospital patients, reduce health care costs for these costs towards the insurance, including the challenge of responding to the needs of society infrastructure financing and supplying hardware explain the lack of adequate supervision, not real tariffs, the imposition of additional costs, inadequate attention to the organizational status of occupational identity, increasing the quality of education and implementation of occupational possible may prepare the groundwork for the government in improving various aspects of quality of service establishment of a competitive environment, health and educational more active use of full-time faculty members, the actual timely commissioning special clinic is a clinic. Conclusion: The development of efficient staff in the health system in order to respond to the needs of society, by creating training opportunities and skills training to achieve clinical competencies possible.Therefore, by clarifying the educational environment and planning the course, and by systematically monitoring and evaluating, it promotes the training and acquisition of clinical competency of interns.